Bat (Chiroptera) viruses of Russia and neighboring countries - A. V. Zhigalin (Юг России: экология, развитие, 2024)
Aim. To analyze the diversity of bat viruses in Russia and neighboring countries. To identify the main vectors of these pathogens and possible ways of introduction into the territory of the Russian Federation.In Russia the RNA sequences of 36 Coronaviridae, 8 Rhabdoviridae and 3 Astroviridae have been obtained from bats. In neighboring countries, RNA/DNA sequences of viruses in bats have been found in Norway (2), Finland 14), Poland 42), Ukraine (8), Georgia (46), Kazakhstan (29), China (5.645) and Japan (109). The dsequences which have been discovered belong to 30 families (Table 1). An increase in the number of sequences obtained over the past year has been observed in Russia and China. The absolute majority of sequences belong to the Coronaviridae family (62.96 %).The available data on bat viruses in Russia indicate the need to develop and implement a state interdisciplinary programme dedicated to this problem. The greatest danger is posed by Rhabdoviridae: mortalities after infection have been recorded in Russia. The data obtained also indicate that the main vectors of viruses are representatives of the genera Eptesicus, Myotis, Nyctalus, Rhinolophus and Vespertilio. The risk of virus exchange and transmission is most likely to be between the western part of Russia and European countries.